1983
DOI: 10.1172/jci110748
|View full text |Cite
|
Sign up to set email alerts
|

Preferential binding of vasoactive intestinal polypeptide to basolateral membrane of rat and rabbit enterocytes.

Abstract: A B S T R A C T Binding of radioiodinated vasoactive intestinal polypeptide (VIP) to intestinal cell membranes of the rabbit ileum and rat jejunum was investigated. Specific binding of '251-labeled VIP could be demonstrated only on the basolateral membrane and not on the brush border membrane. This corresponded with the lack of an effect on ion transport when VIP was applied to the mucosal side of an in vitro preparation of rabbit ileum. VIP altered ion transport only when it was applied to the serosal side. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
16
1

Year Published

1984
1984
2004
2004

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(23 citation statements)
references
References 28 publications
6
16
1
Order By: Relevance
“…The signalling cascade mediated by cAMP leads to the phosphorylation of target proteins by cAMP-dependent protein kinase. It has been reported that VIP receptors are located in intestinal basolateral membranes [27]: as a matter of fact, our results indicate that overlapping effects are obtained when cAMP is substituted by VIP + GTP in the pretreatment of basolateral membranes, whereas VIP has not been tested in brush border.…”
Section: Discussionsupporting
confidence: 46%
“…The signalling cascade mediated by cAMP leads to the phosphorylation of target proteins by cAMP-dependent protein kinase. It has been reported that VIP receptors are located in intestinal basolateral membranes [27]: as a matter of fact, our results indicate that overlapping effects are obtained when cAMP is substituted by VIP + GTP in the pretreatment of basolateral membranes, whereas VIP has not been tested in brush border.…”
Section: Discussionsupporting
confidence: 46%
“…PACAP-38 and VIP have no neuronal component in their respective secretory responses in this tissue. VIP affects epithelial transport processes directly via specific receptors within the basolateral domain (Dharmsathaphorn et al, 1983) and it is probable that PACAP-38 also affects these receptors. Neither of these peptides therefore appear to have a high enough affinity for the neuronal PACAP-27 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The half-maximal stimulation of the adenylate cyclase reported above will therefore be over-estimated 8 VIP AND RENAL FUNCTION 9 by approximately 1P2-fold. Since the relative degradative capacity of renal cortical membranes could conceivably alter the apparent specificity to related hormones, and in particular glucagon, we have determined the relative response of basolateral membranes to both VIP and glucagon in the presence of 1 % w/v bacitracin, a concentration known to completely inhibit the degradation of glucagon by purified basolateral membranes (Talor et al 1983) [125I]VIP in a variety of tissues (Dharmsathaphorn et al 1983;Couvineau & Laburthe, 1985 Fig. 5) compared to cortical tubules, confirming previous workers (Dousa, N. M. GRIFFITHS AND N. L. SIMMONS Shah, & Abboud, 1980).…”
Section: Vip and Renal Functionmentioning
confidence: 99%